Public Sector Transformation Processes and Internet Public Procurement
DOI: 10.4018/978-1-4666-2665-2.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Procurement in the Construction Industry

Abstract: The benefits of e-business have been widely promoted but the Architecture, Engineering, and Construction (AEC) sector has lagged behind other sectors in the adoption of e-procurement. The prospective benefits for the AEC sector are suggested by the proven advantages of general e-procurement where adoption has been faster and deeper. However, several studies indicated that barely 20% of documentation is tendered electronically, suggesting there are barriers to e-procurement. In order to promote adoption of e-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The AEC sector in many countries, including Australia, finds digitalisation challenging (Gajendran and Perera, 2016, Leviäkangas et al, 2017, Stewart et al, 2002, Eadie et al, 2012). E-procurement was the main component of digitalisation in construction a decade ago, and many studies have identified drivers and barriers to digitalisation since then (Eadie et al, 2010, Eadie et al, 2012. Today, the necessity for digitalisation has extended to practices beyond e-procurement and into all aspects of design and construction practices.…”
Section: Introductionmentioning
confidence: 99%
“…The AEC sector in many countries, including Australia, finds digitalisation challenging (Gajendran and Perera, 2016, Leviäkangas et al, 2017, Stewart et al, 2002, Eadie et al, 2012). E-procurement was the main component of digitalisation in construction a decade ago, and many studies have identified drivers and barriers to digitalisation since then (Eadie et al, 2010, Eadie et al, 2012. Today, the necessity for digitalisation has extended to practices beyond e-procurement and into all aspects of design and construction practices.…”
Section: Introductionmentioning
confidence: 99%
“…The research instrument for perceived cost adopted from the study of Eadie et al, (2007), the research items used in the current study "Cost of acquiring and operating the package, less labor-intensive feature of e-Procurement, increase in profit margin associated with e-procurement and e-procurement has high running costs".…”
Section: Methodsmentioning
confidence: 99%
“…As in traditional procurement systems, practitioners may encounter issues such as data security, poor integration with existing systems, and transparency in supply chain operations [54]. The literature highlights that, unlike eprocurement in other industries, such as manufacturing, e-procurement in construction involves highly complex and challenging system operations [55]. While Eadie et al [31] investigated how drivers and barriers to construction e-procurement vary from country to country, Eadie et al [27] examined the drivers and barriers to e-procurement and their perceived differences between public and private organizations.…”
Section: Past Studies On E-procurement Implementationmentioning
confidence: 99%
“…Aduwo et al [43] and Farzin and Nezhad [57] considered high investment costs to be a key economic/financial barrier. Other studies examining barriers to e-procurement highlighted a variety of issues, such as potential cyber-attacks on the supply network [28], security concerns [24], cultural attitudes [58], insufficient ICT infrastructure [43,55], and unreliable power supply [43,55].…”
Section: Studies On Barriers To E-procurement Adoption/implementationmentioning
confidence: 99%